Indonesia's Diplomacy Towards Japan Through The Cultural Instrument Of Tunun Gringsing Bali - Kumala Dewi, Putu Ratih; Cintya Devi, Ni Luh Putu (Intermestic: Journal of International Studies, 2025)
Tunun Gringsing, a traditional Balinese cloth made with the rare double ikat technique, is found in only three countries: Indonesia, Japan, and India. In Japan, it is known as Kurume Kasuri, originating from Fukuoka. This cultural connection between Indonesia and Japan was highlighted at the 2022 Diversity Festival, where both fabrics were exhibited together, emphasizing their role in strengthening bilateral relations. This research aims to describe Indonesia's diplomatic efforts towards Japan using the Tunun Gringsing Bali instrument. This research explores Indonesia's use of Tunun Gringsing as a tool for cultural diplomacy towards Japan, focusing on the actors, activities, and objectives involved. Using qualitative methods, data were collected through interviews and literature reviews. The use of Tunun Gringsing as an instrument of cultural diplomacy is also part of Indonesia's public diplomacy.